2019
DOI: 10.1111/jce.14255
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of subendocardial adipose tissue and fiber orientation distributions in the human left atrium using optical coherence tomography

Abstract: Background Optical coherence tomography (OCT) has the potential to provide real‐time imaging guidance for atrial fibrillation ablation, with promising results for lesion monitoring. OCT can also offer high‐resolution imaging of tissue composition, but there is insufficient cardiac OCT data to inform the use of OCT to reveal important tissue architecture of the human left atrium. Thus, the objective of this study was to define OCT imaging data throughout the human left atrium, focusing on the distribution of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In [42], segmentation was obtained from the variance map through compressive sensing reconstruction. In [38], the distributions of adipose tissues and fiber orientations were retracted and mapped throughout human left atrium, while in [6], the visualization of cardiac fibers in the atrium, ventricle, atrioventricular node, and sinoatrial node were presented. Overall, conventional cardiac OCT image analysis relies on handcrafted features for tissue characterization or fiber orientation-based methods to focus on myofibers.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In [42], segmentation was obtained from the variance map through compressive sensing reconstruction. In [38], the distributions of adipose tissues and fiber orientations were retracted and mapped throughout human left atrium, while in [6], the visualization of cardiac fibers in the atrium, ventricle, atrioventricular node, and sinoatrial node were presented. Overall, conventional cardiac OCT image analysis relies on handcrafted features for tissue characterization or fiber orientation-based methods to focus on myofibers.…”
Section: Related Workmentioning
confidence: 99%
“…Recent advances have demonstrated the capability of OCT on capturing myocardial structures such as Purkinje network [55], atrial ventricular nodes [20], sinoatrial nodes [5], and myofiber organization [18]. In addition, it can be used to resolve critical tissue substrates of arrhythmias, such as fibrosis and adipose tissues [38]. With the development of OCT-integrated catheters [14], OCT can image the heart wall in real time through percutaneous access [51], which holds promise to aid catheter ablation.…”
mentioning
confidence: 99%
“…One specific study utilizing OCT in the left human atria identified adipose tissue near the venous media, within the myocardial sleeves, in the adventitia of the pulmonary veins (PVs), and around the septum. The localization of epicardial fat by OCT‐integrated catheters might thus be helpful for improving the success of AF ablation 44 . However, quality, rather than volume or thickness of the epicardial fat, was found to be an independent risk factor for AF after the first catheter ablation.…”
Section: Obesity Eat and Afmentioning
confidence: 99%
“… 17 , 18 Recently, optical imaging techniques have been applied to the challenge of RFA lesion characterization. Hyperspectral autofluorescence imaging has shown promise in localizing and characterizing RFA lesions, but the complexity of this technique (requiring a hyperspectral camera, UV illumination, and additional optics) renders it less compatible with endovascular access 19 21 Optical coherence tomography has also proven capable of identifying diverse structural substrates, including fibrotic and adipose tissue, 22 27 but tissue penetration depth is limited to 1 to 2 mm.…”
Section: Introductionmentioning
confidence: 99%